(untitled) (Journal of Philosophy Culture and Political Science, 2015)
This article analyzes the International Water Convention, which solved many contentious issues in international water conflicts. Also, based on article outlines the history of the formation within the major international conventions, such as «Helsinki rules using waters of international rivers», «Convention on the law of the non-navigational uses of International watercourses », «Convention on the protection and use of transboundary watercourses and international lakes», «Convention on Environmental Impact Assessment in a Transboundary Context. «Determines the leading role of international water law as the main governing water relations between states at a given time. As part of the article the retrospective analysis, given the set of factor descriptives and examples on how to develop international water law, as well as what policies adhere to the country in resolving transboundary water problems and conflicts.